YOUTH SPORT SPECIALIZATION AND PARENTAL INFLUENCE: A TWO-CITY SURVEY FROM HUNGARY - Nagy, Ágoston; Nagy, Ágoston Botond; Nagy, Ágost Benedek; Borbély, Szilvia (Stadium - Hungarian Journal of Sport Sciences, 2025)
This study explores the role of parental influence in youth sport selection, motivation, and specialization. Parents of young athletes from two Hungarian county seats were surveyed to identify regional differences. Results indicate that parental influence is generally moderate or low but stronger in families with higher financial investment. Specialization increases in adolescence, while younger participants are more likely to try multiple sports. There is a discrepancy between participants and their parents’ competitive aspirations: participants more often aim for the professional level than parents expect. The findings contribute to developing youth sports talent management and parental education in Hungary.